6x+4=4(6x+2)

Simple and best practice solution for 6x+4=4(6x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4=4(6x+2) equation:



6x+4=4(6x+2)
We move all terms to the left:
6x+4-(4(6x+2))=0
We calculate terms in parentheses: -(4(6x+2)), so:
4(6x+2)
We multiply parentheses
24x+8
Back to the equation:
-(24x+8)
We get rid of parentheses
6x-24x-8+4=0
We add all the numbers together, and all the variables
-18x-4=0
We move all terms containing x to the left, all other terms to the right
-18x=4
x=4/-18
x=-2/9

See similar equations:

| 5x-1=3(3x+1) | | 4x+5=2(9x-3) | | 3^5x+3=11 | | (x-4)^2=5 | | -7x+5=-10x+2-5x | | 4-7x=2(3x+8) | | c+34=-c-6 | | r=77=-r-7 | | 7-5x=3(2x-8) | | 5+2d=-13 | | 9x-2=-8x-70 | | 1-5x=4(2x+3) | | 13x+96=360 | | 7(8x+7)=6(5x+2) | | 4/3a-(7/3a+6$=-15 | | -r-4=r+86 | | 138=4(9×3)+2(3h) | | h-41=-h-3 | | c+32=2c | | 6-7x-3=-9+5X-12 | | 2p-3/3=p-1 | | 5^x=2^x-8 | | 8p=6p+72 | | -x+7=x+45 | | 9p-7=5p+9 | | -13=5(x+1) | | b+106=-b+6 | | 7c+8=2c+33 | | 24=3(n- | | 6a-10=5a+2 | | 2(-2+6a)-4=-16+4a | | 4x^2/5=3 |

Equations solver categories